HUBUNGAN TINGKATAN MASLAHAH DALAM MAQASHID AL-SYARI’AH (MASLAHAH AL-DHARURIYAT, AL-HAJIYAT, AL-TAHSINIYAT) DENGAN AL-AHKAM AL-KHAMSAH - Yosi Aryanti (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2017)
Muslim jurists have established a system of Islamic law and establish methods for the discovery of the law giving rise to the methods in istinbat using ushuliyah rules and norms of Islamic law fiqhiyah means of discovery. This means that both of these methods has provided space in tapping the text (nass al-Quran and as-Sunnah) to meet the legal needs of humanity, so that in its development, has led to studies critical that called for Islamic law can be brought benefit for humans and is considered important to be formulated based on essential values called